The Influence of E-Filing Implementation,Service Quality and Tax Knowledge on Individual Taxpayer Compliance - Alfiana Safitri; Umaimah Umaimah (INNOVATION RESEARCH JOURNAL, 2022)
This study aims to determine the effect of the application of e-filing, service quality, and knowledge of taxation on individual taxpayer compliance. The method used is quantitative. The data collection technique used a questionnaire which was distributed to 100 respondents. The method of determining the sample using purposive sampling. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the implementation of e-filing and service quality are not significant on individual taxpayer compliance, while tax knowledge has a significant effect on individual taxpayer compliance.